2016
DOI: 10.1088/1741-2560/13/2/021002
|View full text |Cite
|
Sign up to set email alerts
|

Ethical issues in neuroprosthetics

Abstract: Provided that adequate protections are in place for research subjects and patients, the probable benefit of research into and therapeutic applications of neuroprosthetics outweighs the risk and therefore can be ethically justified. Depending on their neurogenerative potential, there may be an ethical obligation to conduct this research. Advances in neuroscience will generate new ethical and philosophical questions about people and their brains. These questions should shape the evolution and application of nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 153 publications
0
45
0
1
Order By: Relevance
“…Because the avoidance of harm is a basic value in medical ethics, the well-being of the patient, the benefits of the procedure and the potential harm of the intervention need to be balanced carefully. So, similar to other invasive neurotechnologies, the ethical evaluation of benefit and harm is crucial when it comes to the use of invasive BCIs (Glannon 2014(Glannon , 2016, and invasive affective BCIs are no exception here.…”
Section: Affective Bcis and Ethical Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the avoidance of harm is a basic value in medical ethics, the well-being of the patient, the benefits of the procedure and the potential harm of the intervention need to be balanced carefully. So, similar to other invasive neurotechnologies, the ethical evaluation of benefit and harm is crucial when it comes to the use of invasive BCIs (Glannon 2014(Glannon , 2016, and invasive affective BCIs are no exception here.…”
Section: Affective Bcis and Ethical Issuesmentioning
confidence: 99%
“…Although the impact of neurotechnology and BCI on the self and personhood has already received some attention (Fenton and Alpert 2008;Glannon 2016;Hildt 2015;Tamburrini 2009), the role of emotions in these issues needs to be considered more thoroughly. Emotions are important for a sense of self and personal identity.…”
Section: Affective Bcis and Directly Stimulating Affective Statesmentioning
confidence: 99%
“…Previous work on the ethical dimensions of neuroprostheses has focused largely on the broader implications of these and similar technologies once they become more widely available [1,2]. In this article, we focus on the local issues of neuroprosthetic research in its current stage of development and their effects on research participants and cli006Eic patients after SCI.…”
Section: When the Research Participant Becomes A Co‐investigatormentioning
confidence: 99%
“…Ethical issues raised by BCI go beyond strict regulatory matters, and include broader concerns with autonomy, agency, responsibility, identity, and normality, and these questions are beginning to gain attention. [1,2] The Gray Matters report of the President's Commission for the Study of Bioethical Issues recently concluded that neuroscientific advance brings with it moral imperatives both to conduct research in ethically responsible ways but also to think deeply about ethical implications of new knowledge of the brain. [3] BCI technology is at the forward edge of neuroscience and provides a unique opportunity to explore such implications.…”
Section: Introduction To Neuroethics and Bcismentioning
confidence: 99%